2013
DOI: 10.1038/ki.2013.207
|View full text |Cite
|
Sign up to set email alerts
|

NALP3-mediated inflammation is a principal cause of progressive renal failure in oxalate nephropathy

Abstract: Oxalate nephropathy with renal failure is caused by multiple disorders causing hyperoxaluria due to either overproduction of oxalate (primary hyperoxaluria) or excessive absorption of dietary oxalate (enteric hyperoxaluria). To study the etiology of renal failure in crystal-induced kidney disease, we created a model of progressive oxalate nephropathy by feeding mice a diet high in soluble oxalate (high oxalate in the absence of dietary calcium). Renal histology was characterized by intratubular calcium-oxalate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
190
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 198 publications
(204 citation statements)
references
References 31 publications
9
190
1
4
Order By: Relevance
“…Although the mechanisms that link the two remain to be elucidated, it is possible that micro-organisms in the collecting system alter the local microenvironment or provide a nidus for stone formation via a mechanism totally independent of plaque. Indeed, recent animal studies demonstrate that the inflammasome, a part of the innate immune system, appears to play an important role in CaOx crystal-mediated renal damage (19,20). It is also conceivable that alterations in the urinary tract associated with microbial growth lead to inflammasome activation and provide a nidus for CaOx stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanisms that link the two remain to be elucidated, it is possible that micro-organisms in the collecting system alter the local microenvironment or provide a nidus for stone formation via a mechanism totally independent of plaque. Indeed, recent animal studies demonstrate that the inflammasome, a part of the innate immune system, appears to play an important role in CaOx crystal-mediated renal damage (19,20). It is also conceivable that alterations in the urinary tract associated with microbial growth lead to inflammasome activation and provide a nidus for CaOx stone formation.…”
Section: Discussionmentioning
confidence: 99%
“…The kidney is predisposed to inflammasome activation, because the concentration of the primary filtrate and the high osmolarity in the renal medulla favor crystal formation after the solubility coefficient of a given salt is exceeded within the tubular lumen (Figure 2A). Indeed, it has been reported that calcium oxalate crystals activate the inflammasome in renal DCs (87), which may cause progressive loss of kidney function over weeks (88). Additional examples of inflammasome-activating nephrotoxic crystals are formed by uric acid (resulting in gout nephropathy) and adenine (89), which is released, for example, during chemotherapy.…”
Section: Intrarenal Inflammasome Activationmentioning
confidence: 99%
“…However, recent evidence suggests that supersaturation of soluble oxalate causes increased expression of nucleotide-binding oligomerization domain-like receptor, pyrin domain 3 (NLRP3) inflammasomes in the kidney that trigger inflammation and potential kidney injury that may be acute or chronic 12 rather than stone formation (nephrolithiasis).…”
Section: Nephrolithiasis Versus Nephropathymentioning
confidence: 99%